Jordan k-derivations of certain Nobuswa gamma rings - Chakraborty, Sujoy; Paul, Akhil Chandra (GANIT: Journal of Bangladesh Mathematical Society, 2012)
From the very definition, it follows that every Jordan k-derivation of a gamma ring M is, in general, not a k-derivation of M. In this article, we establish its generalization by considering M as a 2-torsion free semiprime ?N-ring (Nobusawa gamma ring). We also show that every Jordan k-derivation of a 2-torsion free completely semiprime ?N-ring is a k-derivation of the same. DOI: http://dx.doi.org/10.3329/ganit.v31i0.10308 GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 31 (2011) 53-64